Effect of perinatal factors on cord blood thyroid stimulating hormone levels - Pawar, Vikram A.; Jain, Swati; Pustake, Vaibhav; Pawar , Poonam (International Journal of Contemporary Pediatrics, 2023)
Background: Screening for congenital hypothyroidism (CH) is a routine practice in most developed countries of the world. This can be done by measuring cord blood thyroid stimulating hormone (CBTSH). Apart from foetal thyroid status and iodine nutrition status of the population, many perinatal factors may also affect CBTSH. The influence of these perinatal factors may affect the sensitivity of CBTSH as a screening tool for CH. The present study was carried out to study the influence of various perinatal factors on CBTSH level. Methods: It was a cross sectional study conducted in tertiary care centre in North Maharashtra. 793 new-borns were included in study. Effects of perinatal factors like maternal age, parity, gender of the baby, birth weight, mode of delivery, gestational age, birth asphyxia on CBTSH was analysed with appropriate scientific method. Results: The mean TSH level in the study group was 7.56±3.9 mIU/l. Among the associated factors vaginal delivery, low gestational age, low birth weight and birth asphyxia were significantly associated with elevated CBTSH values. Hence, any rise in cord blood TSH should be seen in the light of these factors. Conclusions: Among all the associated factors, primi-parity, vaginal delivery, low gestational age, low birth weight and birth asphyxia were significantly associated with elevated CBTSH values. However, no association was observed between CBTSH values and gender of the baby and maternal age.